Factors affecting the incidence of birth asphyxia before and after the helping babies breathe training first in Grobogan, Central Java - Firdausy, Dania Emeralda; Radityo, Adhie Nur; Wiyati, Putri Sekar; Sareharto, Tun Paksi (Basic and Applied Nursing Research Journal, 2023)
Introduction: This study aims to examine the association between factors affecting birth asphyxia and its incidence a year before and after HBB first training conducted in Grobogan, Central Java. Methods: This research was an analytical observational preliminary study with a cross-sectional design. Birth records data collected from 30 primary health care from January to December 2020 in Grobogan, Central Java. Data analyzed with a computer statistical analysis program using χ2 test and Fisher's exact test. Result: Based on 191 medical records from infants born during the year before and 186 medical records from infants born during the year after HBB training, there was an 11.5% decrease in the incidence of birth asphyxia compared before and after the training. Results of the χ2 test showed a significant association between the HBB training with the incidence of birth asphyxia (p = 0.014). Before the HBB training, prematurity has a significant association with the prevalence of birth asphyxia (p < 0.001). Furthermore, there is no associated factor that has a significant association with the prevalence of birth asphyxia after the training (p> 0.05). Conclusion: There is a significant decrease in the incidence of birth asphyxia compared between the year after and 1 year before HBB training. Meanwhile, prematurity has a significant association with the incidence before HBB training.